THE EFFECT OF SOUR SOY MILK AND FERMENTED CASSAVA TAPEADDED TO DRINKING WATER TOWARDPRODUCTION AND QUALITY OF CHICKEN MEAT - Okarini, I. A.; Dewi, G. A. M. K.; Bidura, I G. N. G.; Lindawati, S. A; Miwada, I N.S; Miwada, I N.S (Jurnal Peternakan Tropika; Vol 8 No 1 (2020): Volume 8 No. 1 Tahun 2020; Januari - AprilDO - 10.24843/ejpt.2020.v08.i01.p03, 2020)
Now there are many opportunities in the development of production and accompanied by an increase in the quality of broiler chicken meat carcasses through biotechnology engineering, namely the use of Lactic Acid Bacteria (LAB) as probiotics, sourced from a result of fermentation traditional cassava tape and sour soy milk.Completely randomized design (CRD) were used which consisted of six treatments and four  replicates. Each replicate consist of five chickens. The chicken was raised for 5 weeks and then slaughtering was done two times or two chickens in each replicate, so we had 48 sample to be analyzed. The treatments are as follow: drinking water not added probiotic as control (A); 1% of cassava tape in 1 liter water (B);  2% of cassava tape in 1 liter water (C); 1% of sour soymilk in 1 liter water (D); 2% of sour soymilk in 1 liter water (E); 1% of cassava tape + 1% sour soymilk in 1 liter water (F). The experimental commercial diets for starter phase (aged 1-3 weeks) was given councentrate type CP 511 and CP 512 for finisher phase (aged 3-5 weeks). The experiment started used the chicken aged 1 week with average weight of 174 – 181 g/birds. In conclusion of the research, had potential benefits improved for carcass production and quality broiler chicken meat, showed that increase of total protein serum, hight density lipoprotein (HDL) and also increasing organoleptic characteristic, also effect significantly decrease of  total cholesterol and low density lipoprotein (LDL). It was sugested consumed the broiler chicken carcass meat to improved safety and healthy consumers. Keywords: LAB probiotic ; sour soy milk ; cassava tape ; production ; quality ; chicken meat